ENSURING THE PROFESSIONAL-GNOSTIC TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS BASED ON AN INTEGRATIVE APPROACH (TAMADDUN NURI JURNALI, 2025)
This article analyzes the theoretical foundations of the integrative approach to ensuring the professional-gnostic training of teachers. Professional-gnostic competence is an important pedagogical concept, including the teacher's ability to acquire knowledge, analyze it, and apply it in practice. The article includes the main components of this competence - professional-gnostic training, the formation of such skills as the teacher's cognitive activity, analysis, synthesis, generalization, and problem-solving. The possibilities of using problem-based learning, reflexive pedagogy, interactive methods, and information technologies in the educational process are considered.